MODEL TERJEMAHAN AL-QUR’AN TAFSIRIYAH USTAD MUHAMMAD THALIB - Rizqa Ahmadi (Arabic Literature Department, 2015)
Translation is process of transferring idea or searching for matches meaning from the source language to the target language. Translation should pay attention to the rules and methods to ensure equivalence of meaning conveyed in accordance with the original. Translate text should also be treated in accordance with the type and characteristics. Translation of religious texts have different demands with ordinary texts. Religious texts are the word of God, which contains the teachings and should be interpreted according to it’s meant by God. Translate al-Quran is one of them. In this study, the object to be studied is one of the translatoions of the Qur'an Tafsiriyah by Ustad Muhammad Talib. With qualitative descriptive method, using the theory of translation of the Qu’ran Azzarqany and Manna 'al-Qattan are expected to confirm the models and description of their characteristics. After analysis, the conclusion is obtained that translation of the Qur’an Tafsiriyah Ustad Muhammad Thalib belonging to translatios of the Quran interpretation, as theorized by Manna 'al-Qattan. It’s translation characteristics more often refers to a popular interpretation of the holy Quran. In addition, he also determines the parameters, such as logic consideration, and rules of correc language.